New Concepts in Public Service in Tasikmalaya City: Challenges and Opportunities - Sundawa Bahtiar (HK-Publishing, 2022)
AbstractPublic policy as an instrument that synergizes the roles of the government and the public has not run optimally. The phenomenon of several policies being canceled or revised by the Government is an indication that there are still overlapping policies and the low ability to innovate and the willingness to innovate by public officials. For this reason, policy innovations are needed that can substantively provide reinforcement in solving problems in the community. Public policy implementation is the implementation or application of a public policy through programs, activities, actions, or actions in a mechanism that is bound to a certain system. The purpose of writing this article is to find out the general concept of implementing public policies, especially in the Tasikmalaya Regency government office. and the results of this study explain that the implementation of public services is an effort by the state to fulfill the basic needs and civil rights of every citizen for goods, services, and administrative services provided by public service providers. In Indonesia, the 1945 Constitution mandates the state to fulfill the basic needs of every citizen for the sake of their welfare, so that the effectiveness of a government system is largely determined by the good or bad implementation of public services. Public service providers in Indonesia are all state organs such as the Central Government, Regional Government (Province, Regency, City). In this regard, the Preamble to the 1945 Constitution even in the 4th aliena expressly states that one of the objectives of the establishment of the Republic of Indonesia is to promote public welfare and educate the nation's life in a just and prosperous manner.Keywords: Policy, Administration, Government Office AbstrakKebijakan publik sebagai instrumen yang mensinergikan peran pemerintah dan masyarakat belum berjalan secara optimal. Fenomena beberapa kebijakan yang dibatalkan atau direvisi oleh Pemerintah merupakan indikasi masih adanya kebijakan yang tumpang tindih dan rendahnya kemampuan berinovasi serta kemauan untuk berinovasi oleh pejabat publik. Untuk itu diperlukan inovasi kebijakan yang secara substantif dapat memberikan penguatan dalam menyelesaikan permasalahan di masyarakat. Implementasi kebijakan publik adalah pelaksanaan atau penerapan suatu kebijakan publik melalui program, kegiatan, tindakan, atau tindakan dalam suatu mekanisme yang terikat pada suatu sistem tertentu. Tujuan penulisan artikel ini adalah untuk mengetahui konsep umum pelaksanaan kebijakan publik khususnya di lingkungan kantor pemerintahan Kabupaten Tasikmalaya. dan hasil penelitian ini menjelaskan bahwa penyelenggaraan pelayanan publik merupakan upaya negara untuk memenuhi kebutuhan dasar dan hak-hak sipil setiap warga negara atas barang, jasa, dan pelayanan administrasi yang disediakan oleh penyelenggara pelayanan publik. Di Indonesia, UUD 1945 mengamanatkan negara untuk memenuhi kebutuhan dasar setiap warga negara demi kesejahteraannya, sehingga efektifitas suatu sistem pemerintahan sangat ditentukan oleh baik buruknya penyelenggaraan pelayanan publik. Penyelenggara pelayanan publik di Indonesia adalah seluruh organ negara seperti Pemerintah Pusat, Pemerintah Daerah (Provinsi, Kabupaten, Kota). Berkenaan dengan itu, Pembukaan UUD 1945 bahkan dalam aliena ke-4 secara tegas menyatakan bahwa salah satu tujuan berdirinya Negara Kesatuan Republik Indonesia adalah untuk memajukan kesejahteraan umum dan mencerdaskan kehidupan bangsa yang adil dan makmur.Kata kunci: Kebijakan, Administrasi, Kantor Pemerintah